The occurrence and is factors of tuberculosis in children with close contact to adult lung tuberculosis - Ladylove R. Walakandou; Adrian Umboh; Audrey Wahani (Indonesian Pediatric Society, 2010)
Background Tuberculosis (TB) in is children different from TB in adults in terms of the difficulty in making prompt diagnosis, the more progressive course of disease and the high-risk for the occurrence of disseminated TB. Transmission of TB in children mostly originates from adults, which the biggest risk is the index case with positive sputum smear.Objective To find out the incidence of TB in children who have close contact with adult TB patients and to determine some risk factors for the development of childhood TB.Method This cross-sectional study was conducted between March to July 2009. We studied children aged less than 5 years old with close contact, living in the same house with adult TB patients. The diagnosis of TB was made based on National TB scoring system for children.Results Of the 50 children, we obtained 17 (34%) positive children with TB after going through with national TB scoring system for children. There was a significant relationship between AFB positive sputum, passive smokers and residential density (overcrowding), but there was no significant relationship between age, nutritional status, gender of the contact source, and family income per month.Conclusion Only the positive sputum smear has a significant correlation associated with the occurrence of TB in children who have close contact with adult TB patients.